An historical document analysis of the introduction of the Baby Friendly Hospital Initiative into the Australian setting. Issue 1 (February 2017) - Atchan, Marjorie; Davis, Deborah; Foureur, Maralyn
Abstract: Background: Breastfeeding has many known benefits yet its support across Australian health systems was suboptimal throughout the 20th Century. The World Health Organization launched a global health promotion strategy to help create a 'breastfeeding culture'. Research on the programme has revealed multiple barriers since implementation. Aim: To analyse the sociopolitical challenges associated with implementing a global programme into a national setting via an examination of the influences on the early period of implementation of the Baby Friendly Hospital Initiative in Australia. Methods: A focused historical document analysis was attended as part of an instrumental case study. A purposeful sampling strategy obtained a comprehensive sample of public and private documents related to the introduction of the BFHI in Australia. Analysis was informed by a 'documents as commentary' approach to gain insight into individual and collective social practices not otherwise observable. Findings: Four major themes were identified: "a breastfeeding culture"; "resource implications"; "ambivalent support for breastfeeding and the BFHI" and "business versus advocacy". "A breastfeeding culture" included several subthemes. No tangible support for breastfeeding generally, or the Baby Friendly Hospital Initiative specifically, was identified. Australian policy did not follow international recommendations. There were no financial or policy incentives for BFHI implementation. Conclusions: Key stakeholders' decisions negatively impacted on the Baby Friendly Hospital Initiative at a crucial time in its implementation in Australia. The potential impact of the programme was not realised, representing a missed opportunity to establish and provide sustainable standardised breastfeeding support to Australian women and their families.